2021
DOI: 10.1093/ejcts/ezab441
|View full text |Cite
|
Sign up to set email alerts
|

A new dissection-specific hybrid stent graft for patients with DeBakey type I aortic dissection

Abstract: OBJECTIVES We present our first experience of using a new dissection-specific hybrid stent graft (SG) (the ‘Soft Elephant Trunk’) in the frozen elephant trunk technique, in patients with non-acute DeBakey type I aortic dissection. METHODS Between September 2016 and February 2021, patients with non-acute DeBakey type I aortic dissection underwent the frozen elephant trunk procedure at our centre using 3 SG types: group Z used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A total of 79,931 records were collected via online database review, out of which 7345 studies were eligible for abstract screening. After applying the exclusion criteria, 109 records were adopted for full‐text screening, and eventually, reported data of 43 studies including 5068 patients who underwent TAR with FET were reviewed 4,15–56 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 79,931 records were collected via online database review, out of which 7345 studies were eligible for abstract screening. After applying the exclusion criteria, 109 records were adopted for full‐text screening, and eventually, reported data of 43 studies including 5068 patients who underwent TAR with FET were reviewed 4,15–56 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In November 2020, we performed thoracic aorta repair with the FET technique using dissection-specific hybrid stent graft "Soft Elephant Trunk" 26 mm (MedInzh, Penza, Russia) on a 36-year-old patient with a history of Crawford extent I thoracoabdominal aneurysm and chronic type B 1,10 aortic dissection. 5 The maximum diameter of the descending thoracic aorta (DTA) was 44 mm (Fig. 1), with partial false lumen thrombosis at the level of stent graft (Th9) and an additional 3.7 mm fenestration at the diaphragm level (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…In contrast, Thoraflex Hybrid TM was associated with an early mortality rate of 6% at one Hannover centre. Notably, Song et al reported 0 in-hospital mortalities in 16 patients treated with Cronus TM for ATAAD in Xiamen, China, between February 2018 and August 2019; while Charchyan et al more recently reported that though the difference in mortality rates between Thoraflex Hybrid TM and E-Vita TM for non-acute DeBakey type I aortic dissection were insignificant, Thoraflex Hybrid TM was associated with improved morbidity rates and freedom from dSINE (17,18).…”
Section: Mortalitymentioning
confidence: 99%